BSACI guideline for the set‐up of penicillin allergy de‐labelling services by non‐allergists working in a hospital setting. Issue 10 (21st September 2022) - Savic, Louise; Ardern‐Jones, Michael; Avery, Anthony; Cook, Tim; Denman, Sarah; Farooque, Sophie; Garcez, Tomaz; Gold, Rochelle; Jay, Nicola; Krishna, Mamidipudi Thirumala; Leech, Sue; McKibben, Shauna; et al.
Abstract: The Standards of Care Committee of the British Society for Allergy and Clinical Immunology (BSACI) and a committee of experts and key stakeholders have developed this guideline for the evaluation and testing of patients with an unsubstantiated label of penicillin allergy. The guideline is intended for UK clinicians who are not trained in allergy or immunology, but who wish to develop a penicillin allergy de‐labelling service for their patients. It is intended to supplement the BSACI 2015 guideline "Management of allergy to penicillin and other beta‐lactams" and therefore does not detail the epidemiology or aetiology of penicillin allergy, as this is covered extensively in the 2015 guideline (1). The guideline is intended for use only in patients with a label of penicillin allergy and does not apply to other beta‐lactam allergies. The recommendations include a checklist to identify patients at low risk of allergy and a framework for the conduct of drug provocation testing by non‐allergists. There are separate sections for adults and paediatrics within the guideline, in recognition of the common differences in reported allergy history and likelihood of true allergy.